Benign prostatic enlargement is not associated with diabetes: a population‐based study. (27th July 2015) - Chiu, Y. L.; Kao, S.; Lin, H. C.; Liu, S. P.; Huang, C. Y.
Summary The association between diabetes and benign prostatic hyperplasia remains inconclusive. In this case–control study, we examined the association of diabetes with benign prostatic enlargement (BPE) using the Longitudinal Health Insurance Database 2000 in Taiwan. In total, 20 152 patients with BPE as cases and 20 152 age‐matched patients without BPE were included as controls. Conditional logistic regression analyses were performed to calculate the odds ratio (OR) and corresponding 95% CI for having been previously diagnosed with diabetes between cases and controls. We found that of the 40 304 sampled patients, 9492 (23.6%) had a history of diabetes before the index date. This mean age for the sampled patients was 65.9 with a standard deviation of 12.0 years. A Chi‐squared test revealed that there was a significant difference in the prevalence of prior diabetes between cases and controls (25.3% vs. 21.8%, p < 0.001). The conditional logistic regression found that the OR of prior diabetes for cases was 1.21 (95% CI = 1.15–1.27) compared with controls. However, after adjusting for geographic region, monthly income, urbanization level, hypertension, coronary heart disease (CHD), hyperlipidemia, tobacco use disorder, and obesity, the association between prior diabetes and BPE did not reach a statistically significant level (OR = 1.03, 95% CI = 0.98–1.08). In addition, it was noteworthy that hypertension (OR = 1.25, 95% CI = 1.20–1.31), CHD (OR = 1.40, 95% CI = 1.32–1.48), and hyperlipidemia (OR = 1.30, 95% CI = 1.24–1.36) were all significantly associated with BPE. We found that men with a diagnosis of diabetes were not significantly associated with BPE after adjusting for patient's sociodemographic characteristics and comorbidities.